2022
DOI: 10.2106/jbjs.21.00785
|View full text |Cite
|
Sign up to set email alerts
|

Poor Agreement Between Next-Generation DNA Sequencing and Bacterial Cultures in Orthopaedic Trauma Procedures

Abstract: Background: Next-generation DNA sequencing (NGS) detects bacteria-specific DNA corresponding to the 16S ribosomal RNA gene and can identify bacterial presence with greater accuracy than traditional culture methods. The clinical relevance of these findings is unknown. The purpose of the present study was to compare the results from bacterial culture and NGS in order to characterize the potential use of NGS in orthopaedic trauma patients.Methods: A prospective cohort study was performed at a single academic, lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This indicates that mNGS may miss pathogens, be inconsistent with blood culture, have false negative results, and need for higher sequencing depth detection ( Duan et al., 2021a ; Gu W., et al., 2021 ). Natoli et al. (2022) also agreed that any contamination with the blood culture between sample processing and data analysis could bias the final results seriously.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This indicates that mNGS may miss pathogens, be inconsistent with blood culture, have false negative results, and need for higher sequencing depth detection ( Duan et al., 2021a ; Gu W., et al., 2021 ). Natoli et al. (2022) also agreed that any contamination with the blood culture between sample processing and data analysis could bias the final results seriously.…”
Section: Discussionmentioning
confidence: 84%
“…This indicates that mNGS may miss pathogens, be inconsistent with blood culture, have false negative results, and need for higher sequencing depth detection (Duan et al, 2021a;Gu W., et al, 2021). Natoli et al (2022) also agreed that any contamination with the blood culture between sample processing and data analysis could bias the final results seriously. Boers et al (Boers et al, 2019) also showed that the above reasons lead to the discovery of non-existent bacterial genera, false correlations between microbes and their hosts, and the inability to detect true correlations.…”
Section: Discussionmentioning
confidence: 96%
“…Implant sonification and histological analysis have been demonstrated to improve diagnosis of FRI. 34,35 By contrast, next-generation sequencing has shown inconsistent agreement with cultures taken during surgery, and it does not currently have evidence to support its routine use. 36…”
Section: Discussionmentioning
confidence: 99%
“…We note that this limitation is not unique to the present study, but rather is currently the case for the microbiome field in general. Evidence in related subjects such as orthopedic trauma and urinary tract infections, suggests that there is currently insufficient evidence for NGS as a substitute or complement to conventional culture, and additional studies are necessary to determine its clinical utility 20 , 21 . Although there was considerable overlap between the NGS and cuture results in device biofilms in the present study, the clinical utility of NGS for the diagnosis of device-associated infection or to inform treatments for this condition requires further investigation.…”
Section: Discussionmentioning
confidence: 99%